High-quality genome assembles from key Hawaiian coral species. (9th November 2022) - Stephens, Timothy G; Lee, JunMo; Jeong, YuJin; Yoon, Hwan Su; Putnam, Hollie M; Majerová, Eva; Bhattacharya, Debashish
Abstract: Background: Coral reefs house about 25% of marine biodiversity and are critical for the livelihood of many communities by providing food, tourism revenue, and protection from wave surge. These magnificent ecosystems are under existential threat from anthropogenic climate change. Whereas extensive ecological and physiological studies have addressed coral response to environmental stress, high-quality reference genome data are lacking for many of these species. The latter issue hinders efforts to understand the genetic basis of stress resistance and to design informed coral conservation strategies. Results: We report genome assemblies from 4 key Hawaiian coral species, Montipora capitata, Pocillopora acuta, Pocillopora meandrina, and Porites compressa . These species, or members of these genera, are distributed worldwide and therefore of broad scientific and ecological importance. For M. capitata, an initial assembly was generated from short-read Illumina and long-read PacBio data, which was then scaffolded into 14 putative chromosomes using Omni-C sequencing. For P. acuta, P. meandrina, and P. compressa, high-quality assemblies were generated using short-read Illumina and long-read PacBio data. The P. acuta assembly is from a triploid individual, making it the first reference genome of a nondiploid coral animal. Conclusions: These assemblies are significant improvements over available data and provide invaluable resources for supporting multiomics studies into coral biology, not just in Hawaiʻi but also in other regions, where related species exist. The P. acuta assembly provides a platform for studying polyploidy in corals and its role in genome evolution and stress adaptation in these organisms.